Analysis Of Social Structure And Power Relations In NW Anjani Community - Muh. Alwi Parhanudin (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2020)
In Political Sociological perspective, Nahdlatul Wathan is not only present in religious narration of Sasak Community but also has been able to build social structure with certain typical characteristics. Putting Islamic fundamentals, nationality, and NW-ism, the social structure of NW citizens reflects more the communal community, the one with high social interaction intensity and religious character. In its development, the dynamics of Nahdlatul Wathan community in communal dimension reflects a complex power relation, not only in “piety” classification and teacher-student relation but also shifting to education and intellectuality levels, resource ownership, family hegemony, and territorial egocentrism. This article will address the interaction pattern built within NW Anjani-affiliated community and power relation developing within it. This study employed structural-functional theory to read structure and system running, and power-relations theory to read the power developing in the social structure. This study describes that NW Anjani has a variety of basic values remaining to be held on tightly by its citizen as social capital and social interaction glue. The dynamics of NW Anjani community also reveals strong and functional power relation and gives significant implication to the citizen community wholeness. However, the shift of paradigm and social action of most NW Anjani citizens remains to be apparent from communal toward-non communal community, and from authoritative power relation toward symbolic authority resistance.